Enhancing the use of science in environmental policy-making and regulation - Holmes, J; Clark, R (2008)
Over the last 10 years the UK Government has strongly promoted the more effective use of science to inform policy-making and regulation. In response, the Environment Research Funders' Forum (which brings together the main UK Governmental funders of environmental research) has carried out studies, reported in this paper, to establish what is working, what is not, and why in respect of the linkage between science and environmental policy-making and regulation. The findings indicated that there was potential to improve effectiveness in: establishment of research questions and agendas, accessing information and expertise, the role of interpreters, and transparency and evaluation. These findings are re-enforced by those of previous studies conducted in the UK and EU. The studies found that current practice in using science to inform policy-making has not yet caught up with guidance, and they identified potential actions that could be taken by the Forum and its members to narrow the gap. © 2008 Elsevier Ltd. All rights reserved.